Hirsutism and Depression in Polycystic Ovarian Syndrome - Ahmad, Naveed Shehzad; Waheed, Talha; Iftikhar, Mariam; Fatima, Arzinda; Omer, Syed Muhammad; Farooq, Waqas (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the frequency of hirsutism and depression in female patients with Polycystic Ovarian Disease and to investigate the association between depression and hirsutism in such patients.Study Design: Cross-sectional study.Place and Duration of Study: Gynecology and Medical Department of Fatima Memorial Hospital, Lahore Pakistan, from Jan to Jun 2022.Methodology: A total of 118 females who fulfilled the inclusion criteria were enrolled after taking written informed consent. Demographic details, clinical history and physical examination findings were noted on a predesigned proforma. Hirsutism was assessed by the Ferriman-Gallwey Method and depression was assessed according to Beck Depression Inventory. Findings were noted down on the proforma and were subjected to statistical analysis.Results:  The mean age of our patients was 32.9±7.09 years, the mean BMI was 26.9±3.13 kg/m2, the mean Beck Depression Inventory value was 10.7±1.38 and the mean Ferriman Gallwey Score was 7.8±1.53. Hirsutism was seen in 19(16.1%) patients and depression in 22(18.6%) females. In patients who had hirsutism, depression was seen in 18(94.7%) patients and the association between hirsutism and depression was found to be statistically significant with a p-value of